La Sibérie et les peuples sibériens dans l’Encyclopédie de Diderot et d’Alembert - Belissa, Marc (Presses universitaires de Rennes, 2019)
The encyclopaedias and dictionaries of the Enlightenment provide an interesting image of the North. They allow us to understand what the general public reading those encyclopaedias during the eighteenth century knew about this part of Europe. Diderot’s Encyclopédie contains several articles concerning Siberia and the Siberians. These articles give us a rather accurate image of Siberia founded on recent sources (see the works of Gmelin). The description of the “savage” peoples from Siberia is to be understood in relation to the Enlightenment debate about human variety and “civilization.”